ANALISIS KODIKOLOGI NASKAH MUSHAF AL-QUR’AN 20.227 M KOLEKSI KHASTARA: KHAZANAH PUSTAKA NASIONAL - Ilham Abiyusuf; Fadhli Maulana Ihsan; Pakhrurrozi Rozi; Muhammad Fauzi Batubara; Lukmanul Hakim (JIQTA: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
This article examines a Qur’anic manuscript from the KHASTARA Khazanah Pustaka Nasional collection, catalogued as manuscript number 20.227M, originally preserved at the Mpu Tantular Museum in East Java. The study applies a codicological approach to analyze the manuscript’s physical features, including storage conditions, cover, size, writing material, illumination, symbols, and the presence or absence of a colophon. This research is conducted because no previous study has specifically examined this manuscript. The findings show that the manuscript was written on daluang paper using a simplified tsulusi jawi script. Its neat text arrangement and framed layout around each surah reflect careful scribal craftsmanship, although natural deterioration is visible. The absence of a colophon leaves the scribe’s identity and production date unknown. Nevertheless, the manuscript’s characteristics indicate a connection to the Qur’anic manuscript tradition of East Java. This study contributes to understanding the historical, physical, and cultural significance of Qur’anic manuscripts in Indonesia.